(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
The morphological changes of rivers and lakes continue as a result of several factors, including natural and human. These changes include rivers’ pathways, deposition of sediment, erosion, and flooding due to water level fluctuation. It is therefore necessary to understand these changes, which are the basis for the sustainable management of water resources. The Remote Sensing (RS) technique is often regarded as very efficient for monitoring natural events, including the morphological characteristics of river basins. This study has addressed the worldwide morphological changes of rivers and lakes. It has monitored them using modern techniques such as remote sensing techniques and its effectiveness in assessing these changes. Remote sensing technology is an advanced tool brought about a significant shift in the field of studying the morphological changes of rivers and lakes. This technology has provided the capability to collect and analyze data on a large scale, offering precise and up-to-date information about morphological changes not only for aquatic systems but also for landforms and physical alterations. This technology relies on multiple applications for assessing morphological changes, including satellite imaging, LiDAR (Light Detection and Ranging) techniques, and radar systems. The results show the effectiveness of remote sensing techniques and geographic information systems in analyzing and monitoring the morphological changes of rivers, lakes, and the aquatic environment in general, as these techniques save effort, time, and accuracy compared to traditional methods and fieldwork. The findings of this research indicate that remote sensing technology and geographic information systems are highly effective in monitoring morphological changes in rivers and lakes. These methods provide precise results in a significantly shorter timeframe compared to conventional approaches. Additionally, they offer precise and dependable outcomes capable of encompassing extensive regions and gathering crucial and varied information such as terrain heights, water movement, sediment dispersion, and early identification of geological problems.